2019
DOI: 10.1063/1.5116332
|View full text |Cite
|
Sign up to set email alerts
|

Verification of gyrokinetic particle simulation of current-driven instability in fusion plasmas. IV. Drift-tearing mode

Abstract: The drift-tearing instability due to diamagnetic drift effects is verified using the Gyrokinetic Toroidal Code (GTC). First, the classical (2,1) resistive tearing mode is verified in a cylindrical geometry with a fluid model. The dependence of the growth rate of the resistive tearing mode on the beta value of the plasma is obtained and is found to qualitatively agree with the theoretical prediction. A drift-tearing mode is subsequently generated when the equilibrium pressure gradient is significant. In this mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The perturbed electromagnetic field is obtained from the gyrokinetic Poisson equation and both parallel and perpendicular Ampère's law, allowing to retain compressional magnetic perturbations δB [29]. GTC has been originally used to study micro-turbulence in tokamak plasmas [24] before being applied to Alfvén type meso-scales instabilities [61][45] [46] and more recently large scale kinetic-MHD instabilities [25][26][27] [28]. In this paper, the fluid-electron model is used to solve the electron drift kinetic equation (DKE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perturbed electromagnetic field is obtained from the gyrokinetic Poisson equation and both parallel and perpendicular Ampère's law, allowing to retain compressional magnetic perturbations δB [29]. GTC has been originally used to study micro-turbulence in tokamak plasmas [24] before being applied to Alfvén type meso-scales instabilities [61][45] [46] and more recently large scale kinetic-MHD instabilities [25][26][27] [28]. In this paper, the fluid-electron model is used to solve the electron drift kinetic equation (DKE).…”
Section: Discussionmentioning
confidence: 99%
“…The gyrokinetic simulation model is suitable for describing low frequency plasma instabilities including microinstabilities [20], meso-scale Alfven eigenmodes excited by energetic particles [21] and MHD modes driven by the equilibrium current and plasma pressure gradients [21] [22]. Recently, a gyrokinetic simulation model with equilibrium current [23] has been implemented in the gyrokinetic toroidal code (GTC) [24], which was subsequently utilized for linear simulation of internal kink [25], resistive [26] and collisionless [27] tearing modes, and drift-tearing modes [28] in a cylinder or a high aspect-ratio tokamak with circular cross-section. Beside the kinetic contribution to the energy principle's potential energy and the neoclassical polarization in kinetic-MHD simulations, gyrokinetic simulations also contain effects of finite parallel electric field (e.g., mode conversion to kinetic Alfvén wave and driftwave instability drive due to thermal plasma pressure gradients) and off-diagonal terms of the pressure tensor.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the equilibrium density gradient was considered previously in our simulation study of the drift-tearing mode. [12] The results showed that the coupling of drift modes to tearing modes led to a substantial reduction in the growth rate and the production of a real frequency. Furthermore, many theoretical and simulation results have shown that the equilibrium temperature gradient plays an important role in the evolution of the drift-tearing mode.…”
mentioning
confidence: 98%
“…The simulations are carried out with the gyrokinetic toroidal code (GTC), and starting from a previous electromagnetic gyrokinetic model in a toroidal geometry, [24,25] a parallel electron force balance equation was introduced for the simulation of resistive tearing modes [26,27] and drift-tearing modes. [12] In this study, the selected mode numbers are (𝑚, 𝑛) = (2, 1) to eliminate the effects of kink coupling. A safety factor profile of 𝑞 = 1.5 + 1.2𝜓/𝜓 𝑤 + 0.7(𝜓/𝜓 𝑤 ) 2 is used to contain the 𝑞 = 2 rational surface in the simulation region, where 𝜓 is the poloidal flux, with 𝜓 = 0 at the magnetic axis and 𝜓 = 𝜓 𝑤 at the plasma boundary.…”
mentioning
confidence: 99%
See 1 more Smart Citation